2017
DOI: 10.1002/cncr.31029
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer survival in the United States by race and stage (2001‐2009): Findings from the CONCORD‐2 study

Abstract: BACKGROUND Results from the second CONCORD study (CONCORD-2) indicated that 5-year net survival for lung cancer was low (range, 10%–20%) between 1995 and 2009 in most countries, including the United States, which was at the higher end of this range. METHODS Data from CONCORD-2 were used to analyze net survival among patients with lung cancer (aged 15–99 years) who were diagnosed in 37 states covering 80% of the US population. Survival was corrected for background mortality using state-specific and race-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 40 publications
(98 reference statements)
4
49
2
Order By: Relevance
“…It could also be related to improved survival or treatment efficacy of the primary malignancy, thus allowing a longer survival and time for a second primary to develop. For example, the CONCORD‐2 study reported that lung cancer survival improved slightly between 2001 and 2003 and 2004–2009 . On the other hand, the burden of SPM among patients with urinary bladder and kidney and renal pelvis decreased from 2000 to 2014.…”
Section: Discussionmentioning
confidence: 99%
“…It could also be related to improved survival or treatment efficacy of the primary malignancy, thus allowing a longer survival and time for a second primary to develop. For example, the CONCORD‐2 study reported that lung cancer survival improved slightly between 2001 and 2003 and 2004–2009 . On the other hand, the burden of SPM among patients with urinary bladder and kidney and renal pelvis decreased from 2000 to 2014.…”
Section: Discussionmentioning
confidence: 99%
“…If an age‐specific estimate could not be obtained, we merged data for adjacent age groups and assigned the combined estimate to both age groups. If 2 or more age‐specific estimates could not be obtained, we present only the pooled, unstandardized estimates for all ages combined: these estimates are italicized in Supporting Tables 2 and 3 in other articles of this supplement …”
Section: Methodsmentioning
confidence: 99%
“…If 2 or more agespecific estimates could not be obtained, we present only the pooled, unstandardized estimates for all ages combined: these estimates are italicized in Supporting Tables 2 and 3 in other articles of this supplement. [20][21][22][23][24][25][26][27][28][29] For each of the 37 states, we present estimates of age-standardized net survival for each cancer up to 5 years after diagnosis. For convenience, we report cumulative survival probabilities (range, 0-1) as percentages in the range of 0% to 100%.…”
Section: Methodsmentioning
confidence: 99%
“…The overall high percentage of microscopically verified cancers observed for all cancers, and the relatively low percentage of patients with solid tumors for whom stage at diagnosis was unknown, suggests that detailed clinical investigation at the time of diagnosis was performed for the majority of patients with cancer diagnosed during this time period. However, the large and consistent racial disparities described herein are likely due to the fact that cancers diagnosed in black men and women tended both to be diagnosed at a later stage and to have lower survival at each stage of diagnosis . These disparities often appeared within the first year after diagnosis, suggesting that additional factors, such as comorbidities and socioeconomic factors related to limited access to screening, diagnosis, treatment, and follow‐up care, may be relevant.…”
Section: Introductionmentioning
confidence: 99%